Software testing fundamentals : - Hutcheson, Marnie L. (Wiley, 2003)
A highly anticipated book from a world-class authority who has trained on every continent and taught on many corporate campuses, from GTE to Microsoft. First book publication of the two critically acclaimed and widely used testing methodologies developed by the author, known as MITs and S-curves, and more methods and metrics not previously available to the public. Presents practical, hands-on testing skills that can be used everyday in real-life development tasks.